ASSOCIATION BETWEEN CLUSTER OF DIFFERENTIATION 4 COUNT AND THE CLINICAL OUTCOMES OF CEREBRAL TOXOPLASMOSIS IN POSITIVE HIV PATIENTS - Utami Tarigan, Kiking Ritarwan & Irina Kemala Nasution (International Journal of Research Science and Management, 2020)
Background: About 30% to 40% of HIV patients ultimately will develop cerebral toxoplasmosis. Objectives: To determine the relationship between CD4 count and clinical outcomes of cerebral toxoplasmosis in HIV positive patients. Methods: This study uses a cross-sectional design. Sampling was conducted at the Integrated Inpatient Room at H. Adam Malik Hospital Medan. The study sample was taken as many as 31 consecutive subjects. CD4 count and KPS (Karnofsky performance score) examinations were performed. CD4 is calculated using the flow cytometry method. The Karnofsky scale is measured to determine the patient's performance status. Data analysis using fisher's exact test. Results: The demographic characteristics of the research subjects were male (93,5%), age range 34,38 ± 7,67 years, marital status (64,5%), high school education level (74,2%), and entrepreneurial work (64,5%). CD4 count < 100 were obtained in 67.7% of subjects with a median value of 25 (2-480). As many as 77.4 % of subjects had a karnofsky scale value of 70 with a median value of 50 (0-80). There is a significant relationship between CD4 count and clinical outcomes of cerebral toxoplasmosis in HIV positive patients, while CD4 <100 cells / µL can increase clinical risk with a Karnofsky Performance Scale (KPS) score 70 to 1.8 times greater (p = 0.02 and PR = 1.8 and Confidence Interval 95% = 0,95-3,41). Conclusions: There is a significant relationship between CD4 count and clinical outcomes of cerebral toxoplasmosis in HIV positive patients.